ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KETAHANAN EKONOMI KELUARGA PEDAGANG PASAR KEDIRI PADA MASA COVID-19 - Hellen, Christina; Urmila Dewi, Made Heny (Buletin Studi Ekonomi, 2024)
Family resilience is the ability of families to protect themselves from various threats to family life, which will result in ensuring community resilience. The purpose of this study is to analyze the factors that influence family economic resilience during the Covid-19 period. The data used is primary data using structured interviews through questionnaires. The data then analyzed through confirmatory factor analysis (Confirmatory Factor Analysis). The results of the study show that Residence Ownership Status, Per Capita Income, and Family Insurance have a significant effect on Family Economic Resilience during the Covid-19 Period, while Education Financing has no significant effect on Family Economic Security during the Covid-19 Period.